Ligand recognition determinants of guanine riboswitches - Mulhbacher, Jérôme (Oxford University Press, 2007)
Guanine riboswitches negatively modulate transcription upon guanine binding. The aptamer domain is organized around a three-way junction which forms the ligand binding site. Using currently available 89 guanine aptamer sequences, a consensus secondary structure is deduced and reveals differences from the previously identified aptamer consensus. Three positions are found to display different nucleotide requirements. Using a 2-aminopurine binding assay, we show that variations are allowed depending on the aptamer context. However, changes at position 48 markedly decrease ligand binding in a context-independent fashion. This is consistent with previous observations with the adenine riboswitch in which position 48 was proposed to interact with position 74, which normally base pairs with the ligand. The in vivo transcriptional control of endogenous Bacillus subtilis guanine riboswitches was studied using RT-qPCR assays. The ratio of elongated/terminated transcripts is decreased in presence of a high concentration of guanine but is dependent on the riboswitch analyzed. In general, the aptamer-2AP complex affinity correlates well with the in vivo regulation efficiency of the corresponding riboswitch. These studies suggest that core variations of guanine aptamers are used to produce a spectrum of ligand binding affinities which is used in vivo by host riboswitches to perform gene regulation.